Application of game theory in ad- hoc opportunistic radios - Mumtaz, S. (2012)
The application of mathematical analysis to the study of wireless ad hoc networks has met with limited success due to the complexity of mobility, traffic models and the dynamic topology. A scenario based UMTS TDD opportunistic cellular system with an ad hoc behaviour that operates over UMTS FDD licensed cellular network is considered. In this paper, we describe how ad hoc opportunistic radio can be modeled as a game and how we apply game theory based Power Control in ad-hoc opportunistic radio.